2022
DOI: 10.3389/fped.2022.837656
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of ETV6::RUNX1 Fusion Gene in a Hispanic Population

Abstract: ETV6::RUNX1 is a genetic rearrangement of good prognosis in children with acute lymphoblastic leukemia (ALL). In Mexico, its prevalence is low in comparison with Caucasian populations. We developed a novel TaqMan one-step RT-qPCR approach to assess the prevalence of four genetic rearrangements in a cohort of Hispanic children with ALL from Mexico City. The prevalence of common fusion gene transcripts was as follows: TCF3::PBX1 7.7%; BCR::ABL1p190 3.3%; and KMT2A::AFF1 2.8%, and ETV6::RUNX1was observed with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…Our finding could be due to the fact that at the beginning of the study not all participating hospitals sent the leukemia patients' samples for analysis. This assumption is supported by a recent study of our research group where this gene rearrangement was found in 7.5% of ALL pediatric cases such as it has been previously reported (42). In addition, the prevalence of the other gene rearrangements that were analyzed in the present research were similar to the reported in MC and worldwide (1-3%) (42).…”
Section: Frequency Of All By Gene Rearrangementssupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding could be due to the fact that at the beginning of the study not all participating hospitals sent the leukemia patients' samples for analysis. This assumption is supported by a recent study of our research group where this gene rearrangement was found in 7.5% of ALL pediatric cases such as it has been previously reported (42). In addition, the prevalence of the other gene rearrangements that were analyzed in the present research were similar to the reported in MC and worldwide (1-3%) (42).…”
Section: Frequency Of All By Gene Rearrangementssupporting
confidence: 91%
“…These frequencies are similar to those found in other Hispanic populations ( 24 , 25 , 27 29 ), and those reported worldwide ( 13 , 20 , 23 25 , 27 41 ). One important and recurrent finding in the Mexican population with childhood ALL is the low frequency of ETV6-RUNX1 , a gene rearrangement associated with a good prognosis of the disease ( 42 ). Internationally, the prevailing assumption was that these gene rearrangements were the most important ones, which played an important role in the clinic (diagnosis, risk stratification and chemotherapy treatment).…”
Section: Introductionmentioning
confidence: 99%
“…This means that in Mexicans, ETV6-RUNX1 , associated with standard prognosis, is reduced, and rearrangements of CRLF2 and iAMP21 , which confer high risk, are widely represented among Mexican patients. Most of these findings have been replicated and confirmed by other groups in Mexico ( Table 1 ) ( 31 , 32 ), although they must be compared to data from other regions in our country.…”
Section: Epidemiological Considerations In Pediatric Allsupporting
confidence: 79%